2018
DOI: 10.1111/lam.13009
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification ofVibriospecies in the Rio Bravo/Grande and water bodies from Reynosa, Tamaulipas

Abstract: Water quality is associated with public health, as it plays an important role in the transmission and epidemiology of pathogens such as Vibrio, since this species have been responsible for human diseases around the world. This study demonstrated the presence of toxigenic Vibrio species in water bodies in Reynosa surroundings, indicating that water bodies may be a source of public health risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Similarly, Joshi et al [45] reported that none of their Vibrio isolates carrying both tdh and trh genes. A study by Guardiola-Avila et al [7] did not discover the ctxA gene, which is consistent with our findings. In addition, several other researchers have also discovered that this gene may not always present in the environment [58].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, Joshi et al [45] reported that none of their Vibrio isolates carrying both tdh and trh genes. A study by Guardiola-Avila et al [7] did not discover the ctxA gene, which is consistent with our findings. In addition, several other researchers have also discovered that this gene may not always present in the environment [58].…”
Section: Discussionsupporting
confidence: 93%
“…Vibrio spp. such as V. alginolyticus, V. anguillarum, V. harveyi, V. vulnificus, and V. parahaemolyticus are the most common species that cause vibriosis in shrimp [7]. Furthermore, V. parahaemolyticus is one of the several causative agents of shrimp disease that has become more prevalent as global shrimp demand and production have increased [8].…”
Section: Introductionmentioning
confidence: 99%